Uso de tecnologias por crianças e o Modelo CTS no ensino de ciências no Ensino Fundamental I - Mauro, Letícia Baptista de (Universidade Federal de São Carlos, 2022)
This final paper offers a review of the literature about pedagogical practices in Science Teaching at the beginning of Elementary School with the aim of finding discussions about the critical and conscious use of technological means and answer our research problem: what do Science Teaching researchers discuss about the use of technologies by children in Elementary School I in dissertations and theses published in the last decennary? We are theoretically based on the CTS Model that presents science teaching in a critical way, proposes the active participation of students in pedagogical practice, locates the historical moment in which we live and our role in scientific and technological development, in the effort to demystify Science. Developing Scientific Literacy is an evident concern in the early years, aligned with the use of different media and technologies to develop quality education. Scientific Literacy and the CTS Model are alternatives that bring science teaching closer to children's daily lives, starting from previous knowledge to scientific knowledge. The research was carried out in the database of the Brazilian Digital Library of Theses and Dissertations (BDTD) from 2012 to 2022. We selected dissertations and theses that carried out pedagogical practices in science teaching in the early years involving technology. We located eight works that were read and analyzed based on our reading and analysis form. The selected works used some type of technology in their pedagogical practices, or discussed the use and impact of technologies on life in society and on the environment. We observed that these works presented planning and didactic sequences that serve as subsidy and inspiration for the development of pedagogical practice in teaching work.
Use of technologies by children and the CTS Model in science teaching in Elementary School I
Keywords: Ensino de ciências; Tecnologia; Modelo CTS; Alfabetização científica; Science teaching; Technology; CTS model; Scientific literacy; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO